2011
DOI: 10.7557/2.31.1.2034
|View full text |Cite
|
Sign up to set email alerts
|

Selection decisions among reindeer herders in Finland

Abstract: Selection of breeding animals is a tool to improve the revenues in animal production. Information about selection practices and criteria are essential in assessing the possibilities for systematic selection schemes. Attitudes of reindeer herders towards use of selection in improving production were investigated by means of interviews. We interviewed the managers of reindeer herding cooperatives concerning their selection decisions. Fortyfive out of 56 managers answered to the semi-structured questionnaire. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Rönnegård et al (2002) discussed how the late maturing females have low calving rate (despite their good condition) and relates this to reproductive inability. Indeed, a herder will cull a female with a limited productivity (Rönnegård et al, 2002;Muuttoranta & Mäki-Tanila, 2011). Martinez et al (2004a) reported very high correlations (0.94-0.96) between the early and later production, hence the successful production in the rst parity can predict the lifetime performance.…”
Section: Direct-maternal Correlationmentioning
confidence: 99%
See 4 more Smart Citations
“…Rönnegård et al (2002) discussed how the late maturing females have low calving rate (despite their good condition) and relates this to reproductive inability. Indeed, a herder will cull a female with a limited productivity (Rönnegård et al, 2002;Muuttoranta & Mäki-Tanila, 2011). Martinez et al (2004a) reported very high correlations (0.94-0.96) between the early and later production, hence the successful production in the rst parity can predict the lifetime performance.…”
Section: Direct-maternal Correlationmentioning
confidence: 99%
“…e majority of meat is produced from calves born in spring and culled in autumn, and the number and size of autumn calves determine herd productivity. From a herder's perspective the best females should mature early, have high reproductive rate and long productive life (Muuttoranta & Mäki-Tanila, 2011). In addition, Genetic variation in meat production related traits in reindeer (Rangifer t. tarandus) they should take good care of their calves facilitating rapid growth and high survival.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations